2022
DOI: 10.14814/phy2.15159
|View full text |Cite
|
Sign up to set email alerts
|

ATP is an essential autocrine factor for pancreatic β‐cell signaling and insulin secretion

Abstract: ATP has been previously identified as an autocrine signaling factor that is co‐released with insulin to modulate and propagate β‐cell activity within islets of Langerhans. Here, we show that β‐cell activity and insulin secretion essentially rely on the presence of extracellular ATP. For this, we monitored changes of the intracellular Ca 2+ concentration ([Ca 2+ ] i oscillations) as an immediate read‐out for insulin secretion in live cell expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…This starting point led us to the hypotheses that 1) TAs are produced by β-cells in an autocrine fashion and 2) local TA levels in the islet reach high levels and are quite transient. Therefore, this signaling system might act quasi-autonomous similar to the recently described fatty acid-and ATP-based autocrine regulation systems in the islets of Langerhans [12,17]. This hormone-GPCR signaling system differs significantly from more thoroughly described organism-wide adrenergic and muscarinic signaling.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This starting point led us to the hypotheses that 1) TAs are produced by β-cells in an autocrine fashion and 2) local TA levels in the islet reach high levels and are quite transient. Therefore, this signaling system might act quasi-autonomous similar to the recently described fatty acid-and ATP-based autocrine regulation systems in the islets of Langerhans [12,17]. This hormone-GPCR signaling system differs significantly from more thoroughly described organism-wide adrenergic and muscarinic signaling.…”
Section: Discussionmentioning
confidence: 76%
“…Pancreatic β -cells express a multitude of GPCRs [15], such as the fatty acid (FA) receptor GPR40 that was found to mediate the majority of the effects that long-chain FAs have on β -cell activity [16]. In our recent work, we demonstrated the essential role of cellular FAs and ATP for [Ca 2+ ] i oscillations and insulin secretion [12,17]. We found that ATP and endogenous FAs do not only stimulate β -cells, but are secreted by these cells and are required for basal β -cellular activity and insulin secretion [12,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this does include a few outbred stocks (e.g. NMRI [ Pohorec et al, 2022 ; Sterk et al, 2021 ; Stožer et al, 2021 ], CD-1 [ Dahlgren et al, 2005 ; Hauke et al, 2022 ; Scarl et al, 2019 ]), direct comparisons of these to traditional inbred lines are rare ( Pohorec et al, 2022 ), and studies of specific genes often use traditional inbred lines, as wild-derived lines do not respond as well to the conventional assistive reproductive technologies required for genome editing and transgenesis ( Hirose et al, 2017 ; Mochida et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…While this does include a few outbred stocks (e.g. NMRI (53-55), CD-1 (9, 56, 57)), direct comparisons of these to the traditional inbred lines are rare (53), and studies of specific genes often use traditional inbred lines as wild-derived lines do not respond as well to the conventional assistive reproductive technologies required for genome editing and transgenesis (58, 59).…”
Section: Discussionmentioning
confidence: 99%